Environment and Host Affects Arbuscular Mycorrhiza Fungi (AMF) Population - Norahizah Abd Rahim,; Hasnah Md Jais,; Hasnuri Mat Hassan, (Tropical Life Sciences Research, 2016)
The association of arbuscular mycorrhiza fungi (AMF) and roots undoubtedly gives positive advantages to the host plant. However, heavily fertilised soil such as in oil palm plantation, inhibit the growth of mycorrhiza. Thus, the aim of this research is to distinguish and quantify the availability of AMF population and propagules at different sites of an oil palm plantation by Most Probable Number (MPN) assay. In addition, root infection method was employed to observe host compatibility through the propagation of AMF using two different types of hosts, monocotyledon (Echinochloa cruss-galli) and dicotyledon (Vigna radiata). Three different locations at an oil palm plantation were chosen for sampling. Each location was represented by a distinctive soil series, and were further divided into two sites, that is canopy and midway area. Midway site had a greater population of AMF compared to canopy. The result showed that different environments affect the availability of AMF in the soil. Higher number of AMF infection observed in monocotyledon host suggests that the fibrous root system provide a better association with mycorrhiza.